A Rate-Distortion Optimized Coding Method for Region of Interest in Scalable Video Coding. (12th January 2015) - Wang, Hongtao; Zhang, Dong; Li, Houqiang
Abstract : The support for region of interest (ROI) browsing, which allows dropping background part of video bitstreams, is a desirable feature for video applications. With the help of the slice group technique provided by H.264/SVC, rectangular ROI areas can be encoded into separate ROI slices. Additionally, by imposing certain constraints on motion estimation, ROI part of the bitstream can be decoded without background slices of the same layer. However, due to the additional spatial and temporal constraints applied to the encoder, overall coding efficiency would be significantly decreased. In this paper, a rate-distortion optimized (RDO) encoding scheme is proposed to improve the coding efficiency of ROI slices. When background slices are discarded, the proposed method uses base layer information to generate the prediction signal of the enhancement layer. Thus, the temporal constraints can be loosened during the encoding process. To do it in this way, the possible mismatch between generated reference frames and original ones is also considered during rate-distortion optimization so that a reasonable trade-off between coding efficiency and decoding drift can be made. Besides, a new Lagrange multiplier derivation method is developed for further coding performance improvement. Experimental results demonstrate that the proposed method achieves significant bitrate saving compared to existing methods.